2011
DOI: 10.1080/09712119.2011.622929
|View full text |Cite
|
Sign up to set email alerts
|

Maximising embryo production in endangered sheep breeds: in vitro procedures that complement in vivo techniques

Abstract: This study investigated the use of previously superovulated ovaries as a source of oocytes, assessing the competence of them for in vitro embryo production. Two superovulatory treatments were performed: equine Chorionic Gonadotrophin (eCG) plus porcine Follicle-Stimulating Hormone (pFSH) in a single dose or the conventional protocol of six decreasing doses of pFSH. Thirty donor ewes of the endangered Ojalada breed were given either the simplified (group S; n 015) or the decreasing-dose (group D; n 015) treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…After fertilization, cleaved embryos were placed in a culture medium for 8 days. Media used for oocyte collection and IVM, IVF and embryo culture have been previously described 23 …”
Section: Methodsmentioning
confidence: 99%
“…After fertilization, cleaved embryos were placed in a culture medium for 8 days. Media used for oocyte collection and IVM, IVF and embryo culture have been previously described 23 …”
Section: Methodsmentioning
confidence: 99%
“…After fertilization, cleaved embryos were placed in a culture medium for 8 days. Media used for oocyte collection and IVM, IVF and embryo culture have been previously described (Forcada et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…In Rasa Aragonesa ewes superovulated with FSH, Alberio et al (2002) obtained 3.7-6.2 oocytes per ewe and 85% to fertilize, and Hammami (2008) reported 6.6-11.1 oocytes per ewe and 90% selected for fertilization. In this context, results obtained in the present study by those ewes which did not respond to the superovulatory treatment are especially remarkable, since 20-30% of the animals present a lack of response to FSH-based superovulatory protocols (Forcada et al, 2000(Forcada et al, , 2011b(Forcada et al, , 2012. In fact, early luteal regression is assumed as a failed response to superovulation and has also been reported by our group in both Rasa Aragonesa and Ojalada breeds (Forcada et al, 2000(Forcada et al, , 2006(Forcada et al, , 2011a, although always associated with multiple FSH injection protocols, not including eCG (Simonetti et al, 2008;Forcada et al, 2011b).…”
Section: Introductionmentioning
confidence: 82%
“…Thus, after the third embryo collection, ewes are euthanized and their ovaries collected to recover their oocytes to be maturated and fertilized in vitro. Forcada et al (2011b) obtained about 16 embryos per ewe when combining in vivo and in vitro techniques. However, it was observed that the competence of the oocytes recovered at day 7 after oestrus, immediately after embryo flushing from previously superovulated ewes, was lower in those treated with a single dose of eCG plus pFSH than in those ewes treated with the standard pFSH treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation